The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1159/000450818
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Homeopathy Users among Internal Medicine Patients in Germany

Abstract: Background: Homeopathy use continues to grow in many European countries, and some studies have examined the characteristics of patients using homeopathy within the general population. The aim of this study was to identify predictors for homeopathy use among internal medicine patients. Patients and Methods: A cross-sectional analysis was conducted among all patients being referred to the Department of Internal and Integrative Medicine at Essen, Germany, over a 3-year period. The analysis examined whether patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(48 reference statements)
1
3
1
Order By: Relevance
“…The present study reports the findings of data collection conducted in a routine homeopathic outpatient setting using software for case recording and data collection. The demo-graphic data of the patients, such as predominantly younger age group of patients 25 and a higher proportion of female patients than male patients, 16,18,21 are comparable with the available literature. Whilst above 60-year-olds were the least represented in the present study, other data collections found the highest frequencies among the 46 to 60, 16 49 to 64 17 and 40 to 60 18 years age groups.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The present study reports the findings of data collection conducted in a routine homeopathic outpatient setting using software for case recording and data collection. The demo-graphic data of the patients, such as predominantly younger age group of patients 25 and a higher proportion of female patients than male patients, 16,18,21 are comparable with the available literature. Whilst above 60-year-olds were the least represented in the present study, other data collections found the highest frequencies among the 46 to 60, 16 49 to 64 17 and 40 to 60 18 years age groups.…”
Section: Discussionsupporting
confidence: 75%
“…This surpasses the improvement or positive health changes earlier reported to be 76%, 16 70% 17 and 50%. 21 Our numbers for large improvement, however, are lower than two of those earlier studies: 11% compared with 32% 16 and 25%. 17 This study is the outcome of real-world data analysis from 14 health clinics in different parts of India.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…In many studies, the focus was on socio-demographic variables. It was found that primarily middle-aged [8], well-educated women use CAM [16,35] and homeopathic treatments, in particular [4,8,19,35,36]. In addition, reasoning skills have also been examined in relation to CAM belief and use.…”
Section: Determinants and Correlates Of Beliefs In Cam And Homeopathymentioning
confidence: 99%